Aspiration pneumonia related deaths in head and neck cancer patients: a retrospective analysis of risk factors from a tertiary care centre in North India. Issue 7 (16th June 2015) - Madan, R; Kairo, A K; Sharma, A; Roy, S; Singh, S; Singh, L; Kaur, J; Mohanti, B K; Bhasker, S; Upadhyay, A D; Rath, G K
Abstract Background: Aspiration pneumonia is an important cause of death in head and neck cancer patients. This study therefore aimed to evaluate the risk factors associated with aspiration pneumonia in head and neck cancer patients. Methods: Hospital death records from 12 years (2000–2012) were reviewed to obtain the number of deaths. Treatment details and cause of death were analysed. Statistical analysis was performed to identify the risk factors for aspiration pneumonia. Results: The records revealed that aspiration pneumonia was the cause of death in 51 out of 85 patients. Primary tumour site (oropharynx and hypopharynx, odds ratio 3.3; 95 per cent confidence interval 1.17–9.4, p = 0.02) and advanced tumour stage (odds ratio 4.2, 95 per cent confidence interval 1.16–15.61, p = 0.02) had significant negative impacts on aspiration pneumonia related mortality. Conclusion: Advanced pharyngeal cancer patients are at an increased risk of aspiration pneumonia related death. Investigations for the early detection of this condition are recommended in these high-risk patients.